Modal Manusia Memoderasi Pengaruh Kapabilitas Financial Pada Kinerja UKM - Rina Sulistyowati; Rita Nataliawati; Tri Winarsih; Silfa Syabilatul Nabila; Diana Septiya Sari (Jurnal Akademi Akuntansi, 2023)
Purpose: This study is to determine the performance improvement of SMEs in Surowiti Gresik Village through financial capability with human capital as a moderating variable Methodology/approach: The sample determination method used is total sampling with 85 respondents. Questionnaires were used in data collection. The data analysis method used in this study was Structural Equations Modeling with PLS 3.2.7. Findings: The results of the study prove that financial capabilities affect the performance of SMEs and human capital is able to moderate the effect of financial capabilities on the performance of SMEs Practical and Theoretical contribution/Originality: SMEs in Surowiti village need to be aware of the importance of financial capabilities in managing their business so that their business can develop well. It is hoped that this research will be able to contribute as a reference for managing SMEs with good financial knowledge and of course human capital that supports and wants to develop Research Limitation: The results of this research are limited to the SME sector in Surowiti Gresik Village. In the future, research can develop this research by adding SME industries in other villages to expand indicators of financial capability and human capital.